VALUE OF LUNG ULTRASOUND IN THE DIAGNOSIS AND TREATMENT MONITORING OF LOBAR PNEUMONIA IN CHILDREN AT HANOI CHILDREN'S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the value of lung ultrasound in the diagnosis and treatment monitoring of lobar pneumonia in children at Hanoi Children's Hospital.Subjects and Methods: A retrospective, longitudinal follow‑up study was conducted on 171 pediatric patients aged 2 months to 15 years diagnosed with lobar pneumonia at Hanoi Children's Hospital (November 2024 – October 2025). All patients underwent lung ultrasound and chest X‑ray at admission and after 5 days of treatment. The level of agreement between lung ultrasound and chest X‑ray, as well as with clinical and paraclinical criteria, was assessed using the Kappa coefficient.Results: At initial diagnosis, lung ultrasound showed good agreement with chest X‑ray (Kappa = 0.66; 95% CI: 0.54–0.78). After 5 days of treatment, the change in lung ultrasound score (∆ PedPne LUS) and the change in chest X‑ray score (∆ Brixia) demonstrated good agreement (Kappa = 0.63; 95% CI: 0.52–0.74); the agreement with the change in CRP was low (Kappa = 0.24; 95% CI: 0.10–0.38). Compared with clinical response, agreement was moderate (Kappa = 0.38; 95% CI: 0.25–0.51).Conclusion: Lung ultrasound is a reliable, radiation‑free, point‑of‑care tool that supports the diagnosis and monitoring of lobar pneumonia, complementing clinical and laboratory assessments.
Keywords: Lung ultrasound, lobar pneumonia, children.